RADIOFREQUENCY CATHETER ABLATION FOR SUPRAVENTRICULAR TACHYCARDIAS: EXPERIENCE AT PESHAWAR - Awan, Zahid Aslam; Irfan, Mohammad; Shah, Bakhtawar; Noor, Lubna; Khan, Sher Bahadar; Amin, Faisal (Journal of Ayub Medical College Abbottabad, 2009)
Background: Drug therapy is mostly employed in the management of supraventricular tachycardias (SVTs). However, radiofrequency catheter ablation has been found to be highly effective and safe in the treatment of SVTs. The current study is aimed at sharing our experience of 320 patients who presented with SVTs, and were treated with radiofrequency catheter ablation. Methods: This descriptive study was carried out in the Cardiac Electrophysiology Laboratory of Lady Reading Hospital, Peshawar from October 2006 to December 2009. Standard 4-wire electrophysiological study was carried out to identify the mechanism of SVT in 320 consecutive patients. Radiofrequency catheter ablation was used to interrupt the tachycardia circuit. Results: Out of a total 320 patients who underwent electrophysiologic study, 168 were found to have atrioventricular nodal re-entry as underlying mechanism; 121 patients were having accessory pathway responsible for re-entry (of these 95 presented with orthodromic reciprocating tachycardia and 26 as antidromic reciprocating tachycardia); 19 patients were having focal atrial tachycardia, 4 atrial fibrillation and 8 atrial flutter as the underlying cause for SVT. Radiofrequency catheter ablation was used with an overall success of 94% and a complication risk of complete AV block in 0.3% and recurrence rate of 3%. Conclusion: Radiofrequency catheter ablation is safe and highly effective mode of treatment of SVTs. Keywords: Catheter ablation, Supraventricular tachycardia (SVT), Wolf Parkinson White (WPW) Syndrome